Immune Effect of Active Components of Traditional Chinese Medicine on Triple-Negative Breast Cancer - Zhao, Wenjie; Liu, Jinhua; Li, Yaqun; Chen, Zichao; Qi, Dongmei; Zhang, Zhen (Frontiers in Pharmacology, 2021)
Triple-negative breast cancers are heterogeneous, poorly prognostic, and metastatic malignancies that result in a high risk of death for patients. Targeted therapy for triple-negative breast cancer has been extremely challenging due to the lack of expression of estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2. Clinical treatment regimens for triple-negative breast cancer are often based on paclitaxel and platinum drugs, but drug resistance and side effects from the drugs frequently lead to treatment failure, thus requiring the development of new therapeutic platforms. In recent years, research on traditional Chinese medicine in modulating the immune function of the body has shown that it has the potential to be an effective treatment option against triple-negative breast cancer. Active components of herbal medicines such as alkaloids, flavonoids, polyphenols, saponins, and polysaccharides have been shown to inhibit cancer cell proliferation and metastasis by activating inflammatory immune responses and can modulate tumor-related signaling pathways to further inhibit the invasion of triple-negative breast cancer. This paper reviews the immunomodulatory mechanisms of different herbal active ingredients against triple-negative breast cancer and provides an outlook on the challenges and directions of development for the treatment of triple-negative breast cancer with herbal active ingredients.